Research in Interactive Design Vol. 3 Virtual, Interactive and Integrated Product Design and Manufacturing for Industrial Innovation - Fischer, Xavier; Nadeau, Jean-Pierre.; SpringerLink (Online service) (Paris : Springer Paris, 2011)
Research in Interactive Design (vol. 3) presents an in-depth study of new product design methods. Interactive design is an original structured design approach that has recently emerged from transversal research. On the research side, the topic of interactive design is the fruitful result of sophisticated joint studies combining specific numerical engineering theories, original development in design science and industrial engineering, new discoveries in mechatronics and advanced mechanical engineering methods. Additionally, industry benefits from interactive design instruments. Interactive design is a constructive approach that tends to ensure innovation by improving user-integration in the design process, fostering the development of virtual prototypes and providing new powerful ways for collaborative design activities. Interactive design instruments are seen as the extension of traditional CAD tools. This book provides an accurate overview of the recent research or industrial application in interactive design. The different arguments, taken from the international conference Virtual Concept 2010, will provide the reader with some advanced solutions concerning new methods and tools by discussing: - modelling techniques: new techniques ensuring the development of high qualified, up-dated and reduced models being able to represent the behaviour of a process or a product in its environment; - design solution space exploration: specific instruments dedicated to the identification of suitable design solutions and their virtual representation allowing engineers to have interaction with the virtual worlds; - interactive process organization: studies highlighting the basic evolutions of a process integrating new instruments of interactive design. Each subsequent part of the book addresses both advanced techniques and industrial applications of the latest successful research in interactive design. The solutions presented are enhanced by demonstrations of real industrial problem-solving. The different chapters strongly highlight novel solutions for supporting decision-making in a huge field of engineering: product design, manufacturing and assembly, training and risk prevention, Robotics, design for customers, mechanical engineering, etc. In this book, whether a researcher or an industrialist, the reader will find the most recent interactive design techniques and is sure to extract some significant concepts.
Keywords: Engineering; Engineering mathematics; Engineering design; Machinery; Structural control (Engineering).; Engineering; Engineering, general; Engineering Design; Appl.Mathematics/Computational Methods of Engineering; Operating Procedures, Materials Treatment; Manufacturing, Machines, Tools